Agnikarma Unveiled: A Conceptual insight into Agnikarma’s therapeutic potential (AYUSHDHARA, 2024)
Agnikarma, a significant therapeutic technique in Ayurveda, involves the application of heat to specific points on the body for healing purposes. Sushruta, recognized as the father of surgery, meticulously outlined a variety of surgical techniques in conjunction with several parasurgical methods. Among these, 'Agnikarma' is distinguished as a significant parasurgical procedure. Agnikarma is regarded as a highly effective therapeutic procedure, as diseases treated with this method are believed to be free from relapse. Additionally, conditions that are deemed incurable by conventional medicine, surgical interventions, or Kshara applications may find resolution through this therapy. This review article provides a comprehensive analysis of Agnikarma, exploring its historical origins, underlying principles, and clinical applications. We examine the mechanisms by which thermal energy influences physiological processes, including pain modulation and tissue regeneration. The review highlights various methodologies of Agnikarma, such as the types of instruments used and the specific techniques for different conditions, emphasizing its efficacy in managing musculoskeletal disorders, inflammatory diseases, and post-surgical recovery. The article also explores the clinical applications of Agnikarma in addressing conditions that are resistant to conventional therapies.